Development of Learning Module STAIN SAS Babel - Cakrawala, Cakrawala (PASCASARJANA IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2017)
Abstract This study uses a quantitative research. The aim to produce a product. The study consisted of three stages, namely: 1. Reconnaissance 2. 3. Procurement model development product. Questionnaire data were analyzed using simple statistics and interviews were analyzed with descriptive quantitative techniques. Children begin to recognize verbal communication with their environment called the children's language pemerolahan. The first language acquisition occurs when the child who from the beginning without language has now gained one language. At the time of child language acquisition, the child is more directed at the communications functions of the form language.In the field of sistaksis, children begin speaking by uttering a single word. This word for children is actually full sentences, but because he has not been able to say more than one word, he only took one word of the whole sentence.Learning module is needed to assist the student in the learning process diperkuliahan, learning modules for students are good, but need further improvements in order to improve this module book. Based on the research that learning modules for students can improve student learning. Abstrak Penelitian ini menggunakan penelitian kuantitatif. Tujuannya untuk menghasilkan suatu produk. Penelitian terdiri dari tiga tahap, yaitu: 1. Pengintaian 2. 3. Pengembangan produk model pengadaan. Data kuesioner dianalisis menggunakan statistik sederhana dan wawancara dianalisis dengan teknik kuantitatif deskriptif. Anak-anak mulai mengenali komunikasi verbal dengan lingkungan mereka yang disebut pemeriksa bahasa anak-anak. Perolehan bahasa pertama terjadi ketika anak yang sejak awal tanpa bahasa kini telah memperolehsatu bahasa. Pada saat penguasaan bahasa anak, anak lebih diarahkan pada fungsi komunikasi dari bentuk bahasa. Di bidang sistaksis, anak-anak mulai berbicara dengan mengucapkan satu kata. Kata ini untuk anak-anak sebenarnya adalah kalimat penuh, tetapi karena ia belum dapat mengatakan lebih dari satu kata, ia hanya mengambil satu kata dari seluruh kalimat. Modul pembelajaran diperlukan untuk membantu siswa dalam proses pembelajaran yang diperkuliahan, modul pembelajaran untuk siswa baik, tetapi perlu perbaikanlebih lanjut untuk meningkatkan buku modul ini. Berdasarkan penelitian bahwa modul pembelajaran untuk siswa dapat meningkatkan pembelajaran siswa.